A CONCEPTUAL ANALYSIS OF THE DIFFICULTIES AND POTENTIAL HRM TECHNIQUES FOR THE INTERACTION OF MANPOWER WITH ARTIFICIAL INTELLIGENCE - Dr. Aajaz Ahmad Hajam; Alphonsa S John (RADJA PUBLIKA, 2022)
Abstract Objective - This essay intends to particularly address the difficulties that modern organizations' human resource management (HRM) departments and leaders confront as a result of the close interaction between human workers and artificial intelligence (AI)—primarily robots—especially at the team level. On the basis of a conceptual evaluation of the available research, it also offers some prospective solutions that may be helpful to overcome these difficulties. Design, methodology, and approach — To give a very comprehensive yet critical overview of the interaction between AI (especially robots) and HRM in modern organizations, the current study engages in conceptual work that integrates several streams of literature. Results - We emphasize that interactions and teamwork between human workers and robots are evident across a variety of organizational tasks and industries, where both are contributing team members. The HRM function in modern organizations is faced with some particularly difficult challenges as a result of the need to address workers' anxiety about working with AI, particularly in relation to potential job loss and the challenging dynamics of establishing trust between human employees and AI-enabled robots as team members. Along with these, HRM staff members need to carefully handle employee performance evaluations in the future as well as human workers' expectations for task completion with their AI-enabled robot co-workers. When placing human workers in teams with robots, the authors discovered that organizational support mechanisms such as a welcoming climate, training opportunities, and assuring a suitable technological competence level are crucial. Finally, we discovered that one of HRM's most difficult difficulties is performance evaluation in teams where humans and AI (including robots) coexist. We emphasized the possibility of drawing insights from the computer gaming literature, where performance evaluation models have been developed to analyze human and AI interactions while keeping the context and limitations of both in mind. We discussed the lack of frameworks to guide HRM managers in this concern. Originality/value - Our study is one of the few to go beyond a broad or functional analysis of AI in the context of human resource management. It focuses primarily on the teamwork aspect, where human employees and AI-powered robots (robots) collaborate and provide insights and suggestions for such teams' efficient operation.